Cattle Health Monitorng System with Smart Shelter - Santosh S. Nalage; Kagde Amit Santosh; Sawant Ajay Rajaram; Jadhav Rohit Sanjay (International Journal of Solid State Innovations & Research, 2024)
The primary methods of managing cows prior to the development of modern cow health monitoring systems with smart shelters were manual intervention by farmers and traditional processes. These techniques were often less precise and more labour-intensive than modern technical alternatives. Livestock shelters used to often be simple structures, such as sheds or barns, that provided basic weather protection. These shelters lacked modern conveniences like climate control and mechanized feeding systems. The Cattle Health Monitoring System with Smart Shelter, a significant advancement in livestock management, employs technology to improve animal comfort, productivity, and agricultural sustainability. An innovative technology solution to improve the health and care of cattle in farming environments is the Cattle Health Monitoring System with Smart Shelter. This system provides real-time monitoring and analysis of multiple factors relevant to the comfort and health of cattle housed in smart shelters by integrating automation, data analytics, and modern sensors. A network of sensors is integrated within the system to detect and monitor vital indicators like body temperature, humidity, gps tracker, and ruminant sensor. The cloud and IoT system are connected. It offers farmers an economical and effective way to keep an eye on the health of their cattle, which may ultimately result in increased productivity and efficiency in the animal business.
Keywords: Animals; Iot, livestock; cattles; health monitoring; smart shelter